A complex management pathology: treatment experience of osteoporotic fractures in a reference Hospital in Peru - Ponce Manrique, Gian Gabriel; Urquizo Rodríguez, José Luis; Cruz Del Castillo, Víctor Vladimir; Reategui Mesia, Rodrigo Humberto; Adrianzen Castillo, Paul Antonio; Ccallalli-Ruiz, Nino Arturo (Revista Argentina de Neurocirugía, 2026)
Background: osteoporotic vertebral fractures (OVFs) are common in the elderly population, particularly at the thoracolumbar level. They are gaining relevance due to the global demographic transition, which involves an increase in this age group. Objectives: to describe the pre- and post-surgical outcomes of patients treated for OVF and to compare these findings with the related published literature. Methods: medical records of patients with OVF who underwent surgical treatment at our institution between 2022 and 2024 were reviewed. Vertebroplasty was performed in 18 cases, cemented fixation in 1 case, and cemented fixation plus corpectomy in 1 case. The AO Spine classification was used to classify OVFs, the VAS scale was used to assess pain, and the Oswestry scale was used to assess functionality. Statistical analysis was conducted using SPSS®. Results: 20 patients with a mean age of 72.55 years were included; 18 presented with OF3–OF4 fractures. The most common fracture site was the thoracolumbar junction with 13 cases. There were 18 percutaneous vertebroplasties, 1 cemented fixation, and 1 cemented fixation plus corpectomy. The preoperative VAS score: 7.8, and postoperative: 1.7, showing an 80.2% reduction. The Oswestry score improved from 71.5 to 63.3. There were no immediate complications. The average hospital stay was 3 days (range: 1 to 90 days). Conclusion: percutaneous vertebroplasty is a safe and effective treatment for thoracolumbar OVFs, providing significant pain relief and a low complication rate. In elderly patients, being minimally invasive optimizes clinical outcomes.